GAYA KEPEMIMPINAN KEPALA KANTOR WILAYAH AGAMA PROVINSI KEPULAUAN BANGKA BELITUNG DALAM MENINGKATKAN KUALITAS KINERJA PEGAWAI - Budianto, Kun (Universitas Islam Negeri Raden Fatah Palembang, 2019)
The purpose of this study was to determine the leadership style of the Head of the Regional Office of Religion in the Bangka Belitung Islands Province in improving the quality of employee performance. It is expected that the results of this study will find new concepts about policy implementation in the effort to develop Public Administration, particularly in the quality of public services. The results of this study can be used as reference material and also as input for related parties related to research contributions in the Regional Office of Religion. Referring to the purpose of this study which is to find out and analyze the leadership style of the Head of the Religion Regional Office of the Bangka Belitung Islands Province in improving the quality of employee performance, the method used in this study is a descriptive research method or qualitative research design with a case study model. The analysis used in this study is to look at the approach of leadership style theory according to Priansa, autocratic leadership style, Democratic leadership style, and Laissez Faire leadership style. In carrying out his leadership as Head of the Bangka Belitung Islands Province Regional Religious Office, he was more inclined to use the Autocratic leadership style and the Democratic leadership style. While the leadership style of Laissez Faire, was not used because it was not appropriate for the leadership pattern used by the Head of the Religious Region Office of the Bangka Belitung Islands Province.